2006
DOI: 10.1115/1.2160512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Inlet Geometry on the Flow in a Cylindrical Cyclone Separator

Abstract: The use of Gas-Liquid Cylindrical Cyclone (GLLC©) separators for gas-liquid separation is a new technology for oil and gas industry. Consequently, it is important to understand the flow behavior in the GLLC© and the effect of different geometrical geometries to enhance separation. The main objective of this study is to address the effect of different inlet geometries on the flow behavior in the GLLC© by measuring velocity components and the sum of the axial and tangential velocity fluctuations inside the GLLC©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…However, they did not study the effects of the inlet section dimensions. Also Erdal & Shirazi [30] investigated the effect of three different inlet geometries (one inclined inlet, two inclined inlets and a gradually reduced inlet nozzle) on the flow behavior. They reported that, the gradually reduced inlet nozzle geometry is the preferred geometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not study the effects of the inlet section dimensions. Also Erdal & Shirazi [30] investigated the effect of three different inlet geometries (one inclined inlet, two inclined inlets and a gradually reduced inlet nozzle) on the flow behavior. They reported that, the gradually reduced inlet nozzle geometry is the preferred geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The right side of Equation 6is the drag force due to relative slippage of particles and flow. Drag force, generally, is the impelling force and drag coefficient can be computed using Equations 7and (8) and Re P is Reynolds number of the particles which is calculated using Equation (9). Impact of the particles to the walls of the cyclone is treated with elastic coefficient of 0.8 and it is assumed that impact between particles is negligible.…”
Section: Figure 1 Deposition Efficiency On a Single Square In Channelmentioning
confidence: 99%
“…The effect of the angle of entrance was investigated by Qian and Zhang [7], Qian and Wu [8]. Furthermore, Erdal and Shirazi [9] studied three different geometries for entrance namely tilted single entrance, tilted double entrance, conical entrance and their effect on flow behavior inside the cyclone. Zhao et al [10] compared three different entrance geometries namely single tangent entrance, direct symmetrical helical entrance and converging symmetrical helical entrance using a function of particle size and flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Untuk LCO, hasil penelitian ini sejalan dengan penyelidikan sebelumnya terkait Leq, zero-net liquid flow holdup dan daerah pengoperasian (operational envelope). Parameter bentuk inlet lebih lanjut dikembangkan oleh Erdal dan Shirazi [6] dengan mencoba saluran inlet tangensial tunggal, ganda dan mengadopsi prinsip nosel, meskipun penelitian ini belum memberikan perbaikan kinerja GLCC yang signifikan untuk geometri "gradually reduced inlet nozzle" jika dibandingkan dengan bentuk lainnya.…”
Section: |Rotasiunclassified